The impact of the EU–Turkey agreement on the number of lives lost at sea - Irene Tafani; Massimo Riccaboni (Humanities & Social Sciences Communications)
Abstract The European Union is facing a major challenge: irregular migration. Our aim in this paper is to shed light on a past EU migration policy through the lens of a rigorous analysis of its impact. To this end, we look at the EU–Turkey statement, an agreement reached in March 2016 to contrast irregular migration from Turkey to the EU. Despite the intention to curb migration flows, combat smuggling and improve border security, the implementation of the EU–Turkey deal has raised questions about its effectiveness and humanitarian impact. Drawing on existing literature and empirical data, this study examines the impact of the EU–Turkey statement on migration patterns and fatalities in the Mediterranean. Using a Matrix Completion estimator for panel data, we assess the effect of the agreement by quantifying the number of migrants diverted to alternative routes and estimating the lives lost at sea as a result. Our results show a significant diversion effect from the Eastern Mediterranean to the Central Mediterranean route, which undermines the core objective of the agreement to reduce border crossings. We estimate an increase of around 2000 migrants on the Central Mediterranean route due to the agreement from April to December 2016. We also find a correlation between the diversion effect and the risk of death on the main migration routes, resulting in a net increase of 45 ± 3 lives lost at sea. Our work highlights the unintended consequences of bilateral migration agreements and emphasizes the need for a broader perspective when designing future policies.